The Impact Of Website Characteristics On Website Stickness : A Moderated-Mediation Model Of Trust - Yeap,, Jasmine Ai Leen (2012)
In this current competitive digital economy, website stickiness has emerged as a much coveted element among online retailers. The interface design and personality aspects of a website are believed to have an impact on website stickiness. However, trust is believed to play a very crucial role in the relationship between the website’s characteristics and website stickiness. Focusing on first time encounters to a website, this study examined initial trust as a mediator for the relationship between website interface design (structure, content, graphic and social-cue design), website personality (sincerity, excitement, competence and sophistication) and website stickiness.